Understanding Consumer Self-Design Abandonment: A Dynamic Perspective - Krause, Franziska; Franke, Nikolaus (Journal of Marketing, 2024)
Many studies have found that allowing customers to self-design products using customization configurators generates high value for customers. However, in practice, high abandonment rates cast doubt on these findings. In the present article, this contradiction is resolved by analyzing consumers’ experiences during the creative process. Six studies provide converging evidence that consumers abandon customization because their valence during the process is U-shaped: initial high expectations prompt consumers to start self-designing in the first place, but they quickly find, to their frustration, that their (interim) design solutions are less attractive and the self-designing process is less enjoyable than they originally anticipated. Unaware that their enjoyment of the process would ultimately increase if they persisted through this phase, they abandon the self-design process altogether. It is only if the consumer overcomes the minimum of the U of valence that they harness the potential value from self-designing. This problematic pattern can be managed by providing social feedback during the self-design process. These findings contribute not only to the customization literature but also more generally to the understanding of consumers’ goal pursuit by enhancing its scope to creative tasks.